2021
DOI: 10.1186/s12348-021-00252-4
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for non-infectious Uveitis and Scleritis

Abstract: Purpose To provide a comprehensive review of rituximab use for the treatment of non-infectious uveitis and scleritis. Methods Review of literature through December 2020. Results Individual data was available for 229 patients with refractory non-infectious uveitis (n = 108) or scleritis (n = 121) who received treatment with rituximab (RTX). Rituximab was generally utilized as third-line or later treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 78 publications
(178 reference statements)
0
12
0
Order By: Relevance
“…105 It produces a positive therapeutic response by depleting the CD20 + B cells that attack various segments of the eye, including disease improvement and remission, which translates into improved visual acuity. 104,106120…”
Section: Resultsmentioning
confidence: 99%
“…105 It produces a positive therapeutic response by depleting the CD20 + B cells that attack various segments of the eye, including disease improvement and remission, which translates into improved visual acuity. 104,106120…”
Section: Resultsmentioning
confidence: 99%
“…The mean terminal half-life is approximately 22 days. A growing number of reports have supported the use of rituximab in some types of NIU [ 50 , 51 , 52 , 53 , 54 , 55 ]. A retrospective study in JIA-associated uveitis showed a decrease in uveitis recurrences in patients who have not previously responded to other biologic therapies [ 50 ].…”
Section: Biologics In Uveitis Treatmentmentioning
confidence: 99%
“…It is essential to rule out underlying demyelinating or malignant disease before anti-TNF initiation. Rescue drugs are not well studied for patients' refractory to MMF, MTX, and anti-TNF therapy but may include tocilizumab, JAK inhibitors, or rituximab, depending on the disease [43][44][45][46].…”
Section: Uveitis Treatmentmentioning
confidence: 99%